Political Institutions and Government Spending Behavior: Theory and Evidence from Iran - Sajjad Faraji Dizaji; Mohammad Reza Farzanegan; Alireza Naghavi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This study examines how quality of political institutions affects the distribution of government budget in Iran. We first introduce a mechanism through which this can shift government expenditure from patronage to more constructive public spending. Using impulse response functions (IRF) and variance decomposition analysis (VDC) on the basis of Vector Autoregressive (VAR) model, our results imply that a positive shock towards more democratic institutions leads to negative and statistically significant response of military spending and positive and statistically significant response of education expenditures. Our results are robust to different political institutional quality indicators, ordering of variables in the VAR and different specifications of government spending categories.
Keywords: H11; H41; P16; O53; O43; 330